(untitled) (Journal of Economic Research & Business Administration, 2015)
In the structure of Kazakhstan’s economy annually increasing proportion of the mining industry, which leads to its onesided development and reduce the overall competitiveness of Kazakhstan’s economy. However, the mining industry would be a consumer of the products and services of the companies belonging to other sectors of the economy and, thus, to promote macro-economic stability, economic modernization and social well-being of the people of Kazakhstan. Local Content – an indicator of the level of technology and industrial-innovative development of Kazakhstan, which is the share of the value of Kazakhstani goods, services and labor resources used in carrying out the activities of enterprises in the Republic of Kazakhstan. The article discusses the need for local content in terms of innovative development of the national economy of Kazakhstan